Law No. 170 of the Year 2025 Promulgating the Law Regulating Certain Provisions of State Ownership in Companies Wholly Owned Thereby or in Which It Participates - جمهورية مصر العربية (The Middle East Library For Economic Services, 2025)
The provisions of this Law and the accompanying Law shall apply with respect to the regulation of certain matters relating to State ownership in companies wholly owned thereby or in which it participates. Their provisions shall apply to companies whose capital is wholly owned by the State administrative body, including ministries, departments, and agencies, as well as local administrative units, bodies with special budgets, public service and economic authorities, and other public legal persons, regardless of the legal system to which they are subject, as well as to companies owned by such companies, whether individually or jointly with the units of the State administrative body or public legal persons. Their provisions shall also apply to the shareholdings of the units of the State administrative body, the entities, and the companies referred to in the second paragraph of this Article in the capital of companies not wholly owned thereby, within the limits of such shareholdings, and without prejudice to the rules and conditions set forth in the articles of incorporation of such companies, their articles of association, or the shareholders’ agreements or investment agreements pursuant to which they were established. The provisions of this Law and the accompanying Law shall not apply to: 1. Companies established pursuant to international agreements, and companies named in special laws regulating their purposes or ownership structure. 2. Shareholdings of State-owned insurance companies in the capital of any of the companies. 3. Companies engaged in activities of a national or strategic dimension, as determined by a decree of the Cabinet, based upon a joint proposal by the competent minister and the authority concerned at the owning entity. Article: 2 The provisions of this Law and the accompanying Law shall not prejudice the provisions of the Capital Market Law promulgated by Law No. 95 of 1992, the Law Regulating the Supervision of Non-Banking Financial Markets and Instruments promulgated by Law No. 10 of 2009, Law No. 14 of 2012 concerning the Integrated Development of the Sinai Peninsula, Law No. 127 of 2015 authorizing public legal persons to establish joint stock companies, Law No. 177 of 2018 establishing the Sovereign Fund of Egypt for Investment and Development, and the Central Bank and Banking System Law promulgated by Law No. 194 of 2020. Article: 3 The Prime Minister shall issue the necessary decrees enforcing the provisions of this Law and the accompanying Law, in particular the State Ownership Policy Document. Pending the issuance of such decrees, the existing decrees shall remain in force to the extent that they do not contravene their provisions. Article: 4 Article (27) of the Public Sector Authorities and Companies Law promulgated by Law No. 97 of 1983 shall be repealed, together with any provision that is inconsistent with the provisions of this Law and the accompanying Law. Article: 5 This Law shall be published in the Official Journal and shall enter into force on the day following the date of its publication. This Law shall be sealed with the seal of the State and be enforced as one of its laws.